Demographic potential of childhood in the Republic of Sakha (Yakutia) - Fedotova N. D. (Interactive science, 2018)
on the basis of the analysis of the main demographic indicators of the child population of Yakutia, the problem of the demographic potential of the republic is considered in the varticle. The materials of the All-Russian Population Census, statistical materials of the Territorial Body of the Federal State Statistics Service for the Republic Sakha (Yakutia) were used as the basis for the study. The positive and negative features of the dynamics of demographic indicators are highlighted.
Keywords: дети; рождаемость; Якутия; смертность; численность; children; сельская местность; Yakutia; естественный прирост; mortality; городская местность; number; birth rate; natural growth; urban area; rural area